Surgical treatment of Cervical Dystonia: A Single Center study (Nepal Journal of Neuroscience, 2025)
Introduction: Dystonia is a movement disorder characterized by involuntary, sustained, and patterned muscle contractions, which cause twisting and repetitive movements. Dystonia includes various types of movement disorders such as cervical, generalized and task specific focal hand dystonia. Several potential stereotactic targets have been suggested for the treatment of dystonia such as GPi ( Globus pallidus internus) and PTT (Pallidothalamic tract) for generalized and cervical dystonia and Thalamotomy for task specific focal hand dystonia.Materials and Methods: All the patients of cervical dystonia who underwent surgical interventions in Annapurna Neurological Institute and Allied Sciences since January 2015 till December 2023 were included in our study. We performed unilateral pallidotomy or pallidothalamic tractotomy for cervical dystonia. We used ZD Fishers frame and the thermal lesioning machine of Cosman Radiofrequency (RF) generator with the lesioning electrode of 0.75 mm internal diameter and 2 mm exposed tip was used.Results: There were altogether 42 cases of cervical dystonia. Twenty nine cases had unilateral Pallidotmy and thirteen cases had unilateral pallidothalamic tract (PTT) lesioning. The mean age was 41.49 years±12 years. The male: female ratio was 3:1. The mean percentage change in BFMDRS was 70 percent (p value